Innovative Approaches to Luminescence: Exciton-Polariton Lasers and Quantum Confinement in 2D Materials - Bangshidhar Goswami (International Journal of Photochemistry and Photochemical Research, 2024)
The phenomenon known as luminescence occurs when an external energy of any kind excites a substance's electronic state, and the excited energy is released as light. Luminescence is the absence of heat produced by light emission. Luminescence comes in a variety of forms, including thermoluminescence, bioluminescence, and chemiluminescence. Examples of luminescence include flat-screen TVs, LED lights, and bioluminescent phytoplankton. The measurement of the emission spectrum produced when previously excited atoms or molecules return to their ground state is the foundation of luminescence techniques. Different forms of luminescence are always the result of an energy input of some kind causing light to be emitted. Emissive displays, fluorescent lights, LEDs, and systems that detect X-rays or γ-rays—used in medical imaging, for instance—are among the major applications. In the latter type of applications, high-energy photons excite luminescent materials, and a portion of the excitation energy is converted to visible light. He study delves into exciton lasing fluorophores, emphasizing the potential of plasmon-exciton-polaritons (PEPs) to achieve laser-like emission at low threshold powers. The unique properties of PEPs, facilitated by strong light-matter coupling in metallic nanostructures, are examined, highlighting their potential integration with photonic circuits and metamaterial technologies. Additionally, the article reviews hybrid light-matter lasers, where polariton lasing occurs without the need for population inversion, offering significant benefits over conventional lasers, particularly in terms of operating thresholds.
Keywords: Hybrid light-matter; Photonic circuits; Plasmon-exciton-polaritons (PEPs); conversion; lasers Energy; luminescence